The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1088/1674-1056/ac891f
|View full text |Cite
|
Sign up to set email alerts
|

Antimonene-based saturable absorber for a soliton mode-locked and Q-switched fiber laser in the 2 μm wavelength region

Abstract: In this work, we have demonstrated antimonene as a saturable absorber to generate ultrafast mode-locked and Q-switched laser at a 2-micron wavelength region. The two antimonene-based SAs were prepared and inserted separately in a thulium-holmium doped fiber laser (THDFL) to produce the pulsed lasers. Antimonene was coated onto the tapered fiber to generate soliton mode-locked pulses and in thin-film form for the generation of Q-switched pulses. The modelocking was stable within the pump power of 267 to 511 mW,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Xue et al [ 19 ] assembled antimonene nanosheets on the surface of a gold chip using layer-by-layer technology and found that the sensitivity of antimonene to the SPR sensor varies with different thicknesses, which is defined as the ratio of the change in resonance angle to the change in the refractive index of the analyte, which is at least 2.3 times higher than existing miRNA sensors, even many orders of magnitude higher. It has a high refractive index in ultraviolet [ 20 ] and nonlinear characteristic behaviors [ 21 , 22 ] in optical properties and has applications in lasers [ 23 , 24 ] and laser protection [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Xue et al [ 19 ] assembled antimonene nanosheets on the surface of a gold chip using layer-by-layer technology and found that the sensitivity of antimonene to the SPR sensor varies with different thicknesses, which is defined as the ratio of the change in resonance angle to the change in the refractive index of the analyte, which is at least 2.3 times higher than existing miRNA sensors, even many orders of magnitude higher. It has a high refractive index in ultraviolet [ 20 ] and nonlinear characteristic behaviors [ 21 , 22 ] in optical properties and has applications in lasers [ 23 , 24 ] and laser protection [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…These lasers can be formed in a linear or ring cavity [5]. The doped fibers of rare Earth ions such as thulium, holmium, or thulium-holmium are the suitable gain medium for 2 μm wavelength [6][7][8]. Thulium doped fiber laser (TDFL) can be pumped at 1550 nm having the emission at 1.9 μm.…”
Section: Introductionmentioning
confidence: 99%
“…However, these reports were limited to C-band as the erbium-doped fiber was used as a gain medium for their work. Moreover, due to their limited physical and chemical properties, the new SAs are still being explored [6,[32][33][34]. For instance, graphene has a low damage threshold, and BP can quickly oxidize, so its performance degrades when exposed to air.…”
Section: Introductionmentioning
confidence: 99%